Frequency of Cervical Cancer in Women attending Gynae OPD with Complaint of Abnormal Vaginal Bleeding - Salma Rabbani, Sadia Ahmad, Shumaila Kanwal, Naureen Ghani, Shermeen Kousar, Bushra Bashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The leading cause of death for women in developing countries is cervical cancer and the 3rd most common cause of cancer in women is cervical carcinoma. So proper screening and management screening is vital. Objective: The aim of the study as to explore the Frequency of cervical cancer in women attending Gynae OPD with complaint of abnormal vaginal bleeding. Material and method: The current study was carried out at the department of Gynaecology and Obstetrics, of King Abdullah Teaching Hospital Mansehra and Government General Hospital, Nishtarabad, Peshawar from January, 2023 to June, 2023, after following the permission from the ethical boards of the hospitals. A total of 83 individuals participated in this study. Married women presented to the Gynae OPD with abnormal vaginal bleeding (≥3 menstrual cycles) of reproductive age (18-15 years) were included. Data including, duration of symptoms, party, age, name, age, and parity were collected. The samples were obtained by punch biopsy and examined at the pathology lab. Cervical cancer was confirmed by cervical tissue biopsy and histopathology. Data was analyzed using SPSS version 21 .Data was presented in mean, frequency, standard deviation and percentages. A P value <0.05 was considered significant when the chi-square test was applied. Results: A total of 83 females with abnormal vaginal bleeding were examined out of which 13 (15.6%) were diagnosed with cervical carcinoma. Age groups 36–45 years old had the highest incidence of cervical cancer (8.4%), followed by 26–35 years old (6.2%), whereas women in the 18–25 age group did not have any cervical carcinoma. it was found that 24% of women had five children, which was the highest parity, while 14.4% of women had no kids, 33.7% had one or two children, and 27.7% had three or four children. Individuals who presented with symptoms that lasted longer were shown to have a higher incidence of cervical cancer cases (P value = 0.405) Conclusion: The study concluded that women with abnormal vaginal bleed had high frequency of cervical cancer (15%). Women who are younger and have lower parity are less likely to suffer from this condition. Keywords: Cervical Cancer, cause of death for women, Abnormal Vaginal Bleeding, cervical carcinoma.